2009
DOI: 10.5194/hess-13-1837-2009
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional impact of anthropogenic drainage on fen contiguity

Abstract: Abstract. Knowledge of the hydrological mechanisms behind habitat fragmentation of fen plant communities in intensively managed regions like The Netherlands is essential to improve currently utilized fen restoration and conservation strategies. In this study, we analysed the local and regional impact of anthropogenic drainage on the groundwater supply of fens. For this purpose, we developed finescale groundwater flow models and collected empirical data to analyse (1) the differences in groundwater supply betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…This was also the case in May 2016 although to a minor extent. Furthermore, van Loon et al (2009) showed in a modelling study corroborated with empirical data that in 2006, during periods of precipitation deficit, brackish groundwater were flowing into the fen. Van Loon et al (2009) also suggested that fresh groundwater flow is intercepted by ditches in close-by agricultural land, thereby redirecting it before it can flow to the fen.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This was also the case in May 2016 although to a minor extent. Furthermore, van Loon et al (2009) showed in a modelling study corroborated with empirical data that in 2006, during periods of precipitation deficit, brackish groundwater were flowing into the fen. Van Loon et al (2009) also suggested that fresh groundwater flow is intercepted by ditches in close-by agricultural land, thereby redirecting it before it can flow to the fen.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, van Loon et al (2009) showed in a modelling study corroborated with empirical data that in 2006, during periods of precipitation deficit, brackish groundwater were flowing into the fen. Van Loon et al (2009) also suggested that fresh groundwater flow is intercepted by ditches in close-by agricultural land, thereby redirecting it before it can flow to the fen. However, we stress that the groundwater that seeps up in the major part of the studied fen comes from a regional freshwater system and is still seeping up into the fen in dry periods.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…For example, discharge of deep groundwater into a riparian area is associated with low water temperature, low amounts of nutrients, and a steady supply of water (Almendinger and Leete, 1998;van Loon et al, 2009), whereas shallow groundwater can have high levels of nutrients, in particular in catchments with high agricultural activity (Allan et al, 1997;Davies and Neal, 2007). Because diff erent groundwater sources provide habitats for diff erent community types spanning from high-productive types (e.g., high tall herb fringes) to very low-productive types (e.g., alkaline fens) (DeMars et al, 1997;Wassen et al, 2003;Grootjans et al, 2006), a high community richness is likely to evolve in areas with discharge of diff erent types of groundwater (Jansson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Managed fens often have an anthropogenically controlled hydrology to accommodate multiple land uses like housing and agriculture. Tile drains and ditches (Schot et al, 2004;Van Loon et al, 2009b) and groundwater abstractions (Fojt, 1994), for example, intercept groundwater that is potentially directed to the fen surface, and prevent the available groundwater from entering the fen root zone. Furthermore, drainage elements accelerate the discharge of groundwater from fens via surface water, and often prevent the reinfiltration of groundwater into the fen root zone (Wassen et al, 1990).…”
Section: Implications For Hydrological Fen Restorationmentioning
confidence: 99%